Clinical Evaluation of Maxillary Anterior Teeth in Relation to Golden Proportion, Red Proportion and Golden Percentage - Maharjan, Anjana; Joshi, Sarita (Journal of Nepal Health Research Council, 2018)
Background: Golden proportion, recurrent esthetic dental proportion and golden percentage are the widely accepted tools to measure perceived mesiodistal width of maxillary anterior teeth. Our study was aimed to identify appropriate tool among the above mentioned proportion to measure perceived mesiodistal width.Methods: A cross-sectional observational study was conducted in National Academy of Medical Sciences, Bir Hospital, Nepalese Army Institute of Medical Sciences and Patan Academy of Health Sciences between March 2014 to March 2015.Sixty-three respondents were recruited in the study by the convenient sampling technique. Photographs of the maxillary anterior teeth were taken using digital single reflex camera with macrolens. Data analysis was done using SPSS version 17.0 and paired sample t- test was performed.Results: In our study the golden proportion was 14.28% between central and lateral incisor and 12.69% between canine and lateral incisor. Therefore, golden proportion in our scenario doesn’t exist. Recurrent esthetic dental proportion in female Aryans was 71 and 71 on left side and 71and 75 on right side. Golden percentage of respondents was near to values 11, 15, 22, 22, 15, and 12%.Conclusions: Golden percentage is an appropriate anterior tooth proportion which may serve as a guideline for the restoration of anterior tooth. RED proportion is applicable only in Mongoloid female population.